"What makes a successful coach of women - the myth and the reality" - Verdonkschot, J.; Gossé, C.; Panuska, P.; Postiglione, G.; Espersen, M.; Hay, G. (2014 Coaches Conference - Rio, Brazil, 2014)
About performance development, training, training programme, training volume and testing of two successful Czech rowers - a female and a male one.